2017
DOI: 10.1177/1010428317697569
|View full text |Cite
|
Sign up to set email alerts
|

Expression of claudin 1, claudin 4, and claudin 7 in colorectal cancer and its relation with CLDN DNA methylation patterns

Abstract: IntroductionTargeting tumor suppressor genes by epigenetic silencing especially in the promotor region is one of the probable mechanisms of carcinogenesis. 1 However, differential methylation may also occur outside of the promoter region and previous studies have shown that gene expression and tissue differentiation are powerfully affected by such methylation sites. 1,2 So far, there are limited data available on claudin (CLDN), epigenetics, and the relation to claudin protein expression as well as its role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 28 publications
(43 reference statements)
1
39
0
Order By: Relevance
“…Interestingly, claudin expression is in a tissue specific manner [ 29 ]. Victoria and his colleagues have demonstrated that one of the principal reasons of increased relatively increased expression of CLDN1 in CRC is the hypomethylation of its promoter region [ 30 ], which is also identified in our methylation array data ( Supplementary Figure 2 ). Whereas, the different phenomenon was observed in breast cancer, hypermethylation and reduced expression of CLDN1, suggesting that the expression of CLDN1 varies in different tissues [ 31 ].…”
Section: Discussionsupporting
confidence: 69%
“…Interestingly, claudin expression is in a tissue specific manner [ 29 ]. Victoria and his colleagues have demonstrated that one of the principal reasons of increased relatively increased expression of CLDN1 in CRC is the hypomethylation of its promoter region [ 30 ], which is also identified in our methylation array data ( Supplementary Figure 2 ). Whereas, the different phenomenon was observed in breast cancer, hypermethylation and reduced expression of CLDN1, suggesting that the expression of CLDN1 varies in different tissues [ 31 ].…”
Section: Discussionsupporting
confidence: 69%
“…Claudin-7 expression in CRC also has a dual role. IHC showed significantly lower claudin-7 staining intensity in CRC tissue than adjacent non-tumor tissue, 73 78 and abnormal cytoplasmic localization was observed. 73 There was an important association between claudin-7 expression and lymphovascular invasion, neurotropic invasion, lymphocyte status, and tumor grade.…”
Section: The Dual Relationship Between Claudin-7 and Colorectal Cancementioning
confidence: 91%
“…IHC showed significantly lower claudin-7 staining intensity in CRC tissue than adjacent non-tumor tissue, 73 78 and abnormal cytoplasmic localization was observed. 73 There was an important association between claudin-7 expression and lymphovascular invasion, neurotropic invasion, lymphocyte status, and tumor grade. 74 76 , 79 A decrease in claudin-7 mRNA levels is an early event in the development of CRC that may contribute to the damage of the epithelial barrier in adenomas.…”
Section: The Dual Relationship Between Claudin-7 and Colorectal Cancementioning
confidence: 91%
See 1 more Smart Citation
“…There is accumulating evidence that alterations in DNA methylation contribute to the deregulation of claudin expression in cancer. For example, colorectal cancer tissue showed DNA hypomethylation of the claudin-1 gene as well as reduced membrane expression and increased cytoplasmic expression of claudin-1, as compared with adjacent non-neoplastic mucosa ( 18 ). Ovarian cancer cells that exhibit high expression of claudin-3 showed increased DNA methylation and enhanced histone H3 acetylation of the promoter region ( 19 ).…”
Section: Introductionmentioning
confidence: 99%